Prednisolone for the first rhinovirus‐induced wheezing and 4‐year asthma risk: A randomized trial. Issue 6 (6th August 2017) - Koistinen, Annamari; Lukkarinen, Minna; Turunen, Riitta; Vuorinen, Tytti; Vahlberg, Tero; Camargo, Carlos A.; Gern, James; Ruuskanen, Olli; Jartti, Tuomas
Abstract: Background: Previous findings show that corticosteroid treatment during the first acute wheezing episode may reduce recurrent wheezing in children with high rhinovirus genome load at 12‐month follow‐up. Longer‐term effects have not been investigated prospectively. Methods: After PCR confirmation of rhinovirus from nasopharyngeal aspirate, 79 children with the first acute wheezing episode were randomized to receive orally prednisolone or placebo for 3 days. The initiation of asthma control medication before the age of 5 years was confirmed from medical record and/or from parental interview. The outcome was the time to initiation of regular asthma control medication. Interaction analysis examined rhinovirus genome load. Results: Fifty‐nine (75%) children completed the follow‐up. Asthma control medication was initiated in 40 (68%) children at the median age of 20 months. Overall, prednisolone did not affect the time to initiation of asthma control medication when compared to placebo ( P =.99). Rhinovirus load modified the effect of prednisolone regarding the time to initiation of asthma control medication ( P ‐value for interaction=.04). In children with high rhinovirus load (>7000 copies/mL; n=23), the risk for initiation of medication was lower in the prednisolone group compared to the placebo group ( P =.05). In the placebo group, asthma medication was initiated to all children with high rhinovirus load (n=9) during the 14 months after the first wheezing episode. Conclusions: Overall, prednisolone did not affect the time to initiation of asthma control medication when compared to placebo. However, prednisolone may be beneficial in first‐time wheezing children whose episode was severe and associated with high rhinovirus load. (ClinicalTrials.gov, NCT00731575). Abstract :